Islet Identity in Patients with Pancreatitis. (July 2018) - Sabek, Omaima; Beamish, Christine; Fraga, Daniel; Gaber, A Osama
Abstract : Objective: Total pancreatectomy (TP) and islet auto-transplantation (IAT) is a treatment for chronic pancreatitis; however, its projected success largely relies on transplanted islet equivalent, and defined by post-surgical insulin-injection independence and HbA1c. Endocrine-cell dedifferentiation has been suggested to contribute to metabolic failure in type 2 diabetes, shown by the co-localization of insulin with glucagon and/or vimentin. Here, we correlate islet phenotypic identity with pre- and post-surgical metabolic function following TPIAT in two patients. Research Design and Methods: Metabolic function was compared with histological assessment of endocrine cells demonstrating variable co-expression of insulin and glucagon. Results: Patient 1 demonstrated high endocrine cellular phenotypic maintenance and remained insulin-injection free at study completion. Conclusion: Endocrine-cell dedifferentiation was identified prior to TPIAT, which correlated with pre- and post-surgical endocrine function and transplant endpoints, and may contribute as a predictor of interventional success. Vivian Smith Foundation. Brown Foundation.